Addressing curriculum decolonisation and education for sustainable development through epistemically diverse curricula. - Padayachee, K.; Matimolane, N.; Ganas, L. (2018)
Transformation in Higher Education has been an ongoing concern in post-apartheid South Africa, especially in light of universities’ expected contribution to economic and socio-political transformation. In particular, curriculum transformation has proved challenging, as evidenced in actions and calls by students in recent years for decolonisation of the curriculum. This study, which formed part of an institutional response to the challenge of curriculum transformation and decolonisation, initially sought to examine perceptions of the term “decolonisation” amongst a group of early career lecturers at a leading university in South Africa. Highlighted in the outcomes of the study was the centrality of personal and contextual relevance in notions of decolonised curricula, the impact of curriculum conversations on lecturers’ well-being, and the broader implications of responsive and relevant curricula for institutional and societal well-being. In this respect, the findings of the study illustrated the similarities of curriculum decolonisation approaches and the concept of education for sustainable development which is underpinned by the goal of global well-being and the common good. Also highlighted was the need for greater balance between Mode 1 (theoretical) and Mode 2 (contextually relevant) knowledge in curricula, leading us to posit that both curriculum decolonisation and education for sustainable development are equally necessary for institutional and broader societal reform and well-being, and that both imperatives may potentially be achieved by focusing on the principles of epistemically diverse curricula
Keywords: Decolonisation; Education for sustainable development; Epistemically diverse curricula